Do Performance-Contingent Incentives Help or Hinder Divergent Thinking? - Kachelmeier, Steven J.; Webb, R. Alan; Williamson, Michael G. (The Accounting Review, 2024)
ABSTRACT Toward the goal of reconciling conflicting arguments on whether performance-based incentives facilitate or impede divergent thinking, we identify a feature common to prior demonstrations of negative incentive effects: they generally involve tasks with only one correct solution. Our first experiment replicates a negative incentive effect when insight problems require “bottom-up” divergent thinking from an unexpected resource to the problem it is uniquely equipped to solve, whereas our second experiment finds a positive incentive effect in the more general case of problems that enable “top-down” divergent thinking from a problem to multiple potential solutions. We also observe a positive incentive effect in a third experiment that measures the time needed to generate a solution to problems that have multiple potential solutions and in a fourth experiment in which participants design insight problems. Overall, our findings suggest that any harmful effects of performance-based incentives are likely restricted to highly constrained settings. Data Availability: Data are available from the authors upon request. JEL Classifications: J33; M14; M41; M52.